2022
DOI: 10.1038/s41598-022-07485-w
|View full text |Cite
|
Sign up to set email alerts
|

Advances in purification of SARS-CoV-2 spike ectodomain protein using high-throughput screening and non-affinity methods

Abstract: The spike (S) glycoprotein of the pandemic virus, SARS-CoV-2, is a critically important target of vaccine design and therapeutic development. A high-yield, scalable, cGMP-compliant downstream process for the stabilized, soluble, native-like S protein ectodomain is necessary to meet the extensive material requirements for ongoing research and development. As of June 2021, S proteins have exclusively been purified using difficult-to-scale, low-yield methodologies such as affinity and size-exclusion chromatograph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…We demonstrated that, with a simple tag-free single multimodal chromatography, the particles produced from a stirred-tank bioreactor could be purified with an efficiently scalable procedure. However, a multi-column design may help to improve the purity profile, such as incorporating a weak anion exchange resin as a capture step in a neutral pH buffer [ 61 ]. Affinity mode can also be featured since the spike protein is heavily glycosylated.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that, with a simple tag-free single multimodal chromatography, the particles produced from a stirred-tank bioreactor could be purified with an efficiently scalable procedure. However, a multi-column design may help to improve the purity profile, such as incorporating a weak anion exchange resin as a capture step in a neutral pH buffer [ 61 ]. Affinity mode can also be featured since the spike protein is heavily glycosylated.…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 S-2P protein (S2P7471) was produced as previously described. 78 Briefly, S2P7471 was expressed and purified from the CHO-DG44 cell line. S2P7471 was clarified through centrifugation and Satopore XLG 0.8/0.2 filters.…”
Section: Methodsmentioning
confidence: 99%
“…Purifying the recombinant spike protein at scales suitable for large-scale manufacturing remains a major challenge [9] , [11] , [12] , [13] , [14] , [15] , [16] . Due to its large size, the purification of this protein using conventional resin-based chromatography is both difficult and inefficient.…”
Section: Introductionmentioning
confidence: 99%